Insurance as catastrophe: A geography of house and contents insurance in bushfire-prone places. (February 2016) - Booth, Kate; Harwood, Andrew
Abstract: Insurance is increasingly identified as the disaster management technique of choice; a benign tool that can be utilised to reduce the impacts of disaster and aid recovery. For householders in disaster-prone places, individual rational agency is assumed to inform decision-making surrounding house and contents insurance purchase. In this paper, we present findings from interviews with householders in places with high bushfire risk that significantly unsettle such accounts. Drawing upon four identified themes – trade-offs, networks, virtue and promise – we observe that for these householders, the uncertainty and anxiety created through a lack of transparency on behalf of insurers, the construction of insurance as an individual endeavour, and the rendering of household materiality as object, renders insurance catastrophic. Attempts at calculation for insurance coverage are momentary rather than monetary; as constituting an entanglement of insurantial moments constructed within conflicting emotions, morality and the familial, rather than fiscal accountancy. For our participants this provides a stronger logic for choosing not to have insurance than for having insurance. We conclude with signposts for further research, including advancing the theorisation of insurance in the context of the everyday.